Development of A Thematic Map of Tourism Potential in Ogan Ilir District, South Sumatra - Myrza Rahmanita; Surya Fadjar Boediman; Sri Mariati; Sofian Lusa (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Community service activities (PKM) carried out in Ogan Ilir Regency were initiated as an answer to the needs of the local community to develop tourism potential by empowering the community through skills training and counseling. The main objective of this PKM is to increase the income and quality of life of local communities by introducing new techniques in tourism management and other supporting skills. The implementation method consists of four stages: first, initial meetings with local governments to explain objectives and build cooperation; second, field survey to collect data through observation and interviews; third, data analysis to compile a thematic map of tourism potential; fourth, Forum Group Discussion (FGD) to present the results and obtain input. The results of these activities show a significant increase in community knowledge and skills regarding tourism management. The community is now more ready to take advantage of local tourism potential which is expected to increase their income and quality of life. Implementation of recommendations from PKM is expected to make a positive contribution to tourism development and community welfare in Ogan Ilir Regency.